A histological study on the effect of pressure therapy on the activities of myofibroblasts and keratinocytes in hypertrophic scar tissues after burn. Issue 5 (August 2015) - Li-Tsang, Cecilia W.P.; Feng, Beibei; Huang, Lin; Liu, Xusheng; Shu, Bin; Chan, Yvonne T.Y.; Cheung, Kwok-Kuen
Highlights: Pressure therapy elicited an early yet positive response of hypertrophic scars (HS). The intervention significantly improved the thickness and redness of HS. Proliferation of basal keratinocytes in HS was inhibited after the intervention. Reduction in myofibroblasts was correlated with increase in apoptosis in dermal layer. Abstract: Although pressure therapy (PT) has been widely used as the first-line treatment for hypertrophic scars (HS), the histopathological changes involved have seldom been studied. This study aimed to examine the longitudinal effect of PT on the histopathological changes in HS. Ten scar samples were selected from six patients with HS after burn and they were given a standardized PT intervention for 3 months while 16 scar samples were obtained on those without PT. The scar biopsies were collected pre-treatment, 1 and 3 months post-intervention for both clinical and histopathological examinations. Clinical assessments demonstrated significant improvement in the thickness and redness of the scars after PT. Histological examination revealed that cell density in the dermal layer was markedly reduced in the 3-months post-pressurized scar tissues, while the arrangement of the collagen fiber was changed from nodular to wave-like pattern. The α-smooth muscle actin immunoreactivity was significantly decreased after 1-month pressure treatment. There was a significant reduction of myofibroblasts population and a concomitant increase in the apoptotic index in the dermal layer in the 3-months' post-pressurized scars. A significant negative correlation was found between the myofibroblasts population and the apoptotic index. The keratinocyte proliferation was found inhibited after PT. Results demonstrated that PT appeared to promote HS maturation by inhibiting the keratinocyte proliferation and suppressing myofibroblasts population, the latter possibly via apoptosis.